The effect of economic downturns on apprenticeships and initial workplace training: a review of the evidence - Brunello, Giorgio [Verfasser] (My University, 2009)
"The existing empirical evidence on the relationship between apprenticeships, initial workplace training and economic downturns, is relatively scarce. The bottom line of this literature is that ratio of apprentices to employees tends to be (mildly) pro-cyclical and to decline during a recession, with the notable exception of the Great Depression, when it rose (at least in England). When broader measures of training are considered, which exclude apprentices, the weight of the evidence is in favour of counter-cyclical training incidence. This paper suggests that a possible reconciliation of these findings is based on recognizing that firms may have incentives to train incumbents during a downturn and at the same time to reduce the recruitment and training of young employees, who are engaged in the transition from school to work." (Autorenreferat, BIBB-Doku)
Vorab veröffentlicht als "IZA DP No. 4326", online zugänglich unter: http://ftp.iza.org/dp4326.pdf [Zugriff 3.1.2011]
Keywords: S 1.3 Berufliche Erstausbildung; G 2.1.1 Ökonomie / Märkte; G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; I 2.2 Europa; Berufsausbildung; Betriebliche Berufsausbildung; Rezession; Wirtschaftsentwicklung; Europa